Antecedents and Consequences of Accounting Information System Utilization: Evidence from Firms in Emerging Markets - Kwaku Kyei Gyamerah; Sylvia Agyeman Addai; Abass Sagoe (Journal of Accounting and Management Information Systems (JAMIS), 2024)
Research Question- Does the effect of accounting information system (AIS) utilization on financial performance vary under different conditions of information quality? Motivation- In spite of the growth of literature on AIS adoption, what drives its utilization and the performance implications is less discussed in both accounting and information systems literature. This paper combines transaction cost economics and institutional theory to examine the motivations (efficiency and legitimacy) driving AIS utilization and its consequences on financial performance of firms. The study further examines the moderating role of information quality in the AIS utilization and financial performance nexus. Data- The proposed model was validated using survey data from 384 managers of manufacturing firms in Ghana. SPSS Amos and Hayes Process were used to validate the model. Findings- Our results revealed that the motivation for AIS utilization among SMEs is legitimacy but not efficiency. We also found that AIS utilization and Information Quality (IQ) both significantly drive financial performance. Finally, we found a significant moderating effect of IQ in the relationship between AIS utilization and financial performance. Contribution- These findings hold multiple implications for managers and owners of businesses as well as implications for theory. The study contributes to the inconsistences in earlier discourse by highlighting the transformative force of information quality in enhancing the performance implications of AIS usage. The findings imply that firms utilize AIS with the hope of enhancing their legitimacy in the eyes of stakeholders rather than its efficiency motive.
Keywords: M15; M41; 650; accounting information system (AIS); utilization; financial performance; information quality and small and medium scale enterprises